Efektifitas pemberian makanan tambahan lokal (PMT) terhadap kesejahteraan ibu hamil: Literature review - Damayanti, Melly; Aminin, Fidyah; Jannah, Rawdatul; Mukodri, Dewi Mey Lestanti; Saputri, Nurul Aini Suria; Jasda, Asmarita; Ikhwan, Zainul; Safitri, Tiyara; Putri, Sabtini Ika; Cintiani, Jeni Cesi (Poltekkes Kemenkes Aceh, 2025)
Background: Providing locally-based supplementary feeding has been proven effective in improving the health status of pregnant women and their babies while also supporting food sustainability and local economic development.Objectives: his article aims to explore the types and benefits of locally-based supplementary foods recommended during pregnancy through a literature review.Methods: This study employed a literature study design using the narrative literature review method by searching for scientific articles in the PubMed, ProQuest, and Google Scholar databases. A total of 26,194 articles were found, and 8 articles were analyzed. The article selection process followed the PRISMA standard guidelines. Articles published between 2015 and 2024 were included. The search was conducted using the keywords